Diagnosis, Evaluation, and Management of Diseases during Pregnancy - Craina, Marius L.; Bernad, Elena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes studies on diagnosing, evaluating and managing the pathologies diagnosed during pregnancy. The information provided in these pages is helpful for specialists in obstetrics and gynaecology but also for other medical specialities involved in treating pregnant women with associated pathologies. Studying the articles in the reprint could contribute to improving case management.